Spatial planning for climate change adaptation : developing a climate change local area adaptation plan for Khayelitsha - Mashila, Thabang (University of Cape Town, 2015)
Includes bibliographical references. === Climate change is now widely seen as a major challenge of this time and the future of cities. However, the most vulnerable will be the urban poor particularly those located on the urban fringes in high risk areas with limited access to basic services and economic opportunities. In South Africa, although progress has been made to reduce socio-economic and environmental challenges created by apartheid legislations, inequalities still exist where the privileged live in safer and well located and serviced parts of the city while he poor are still located in settlements created by apartheid in urban fringes. Spatial Planning presents an opportunity to increase resilience to climate change in vulnerable areas of cities. Through integrating planning and climate adaptation actions, future spatial decisions will add to resilience to climate change and enhance wellbeing of people. The dissertation includes a case study that was conducted to learn about the status quo of the study area to effectively recommend relevant interventions that seek to create resilience to climate change in the area. A local area adaptation plan was then formulated including the framework for implementing proposed interventions in a 20 year timeframe.